Prediction of Etawa Goat Productivity using Decision Tree Algorithm and Optimized with Particle Swarm Optimization - Muhamad Nasim; Purwanto; Catur Supriyanto (Department of Informatics, Faculty of Science and Technology, UIN Prof. K.H. Saifuddin Zuhri, Purbalingga, Indonesia, 2026)
The productivity of Etawa goats is influenced by various factors, including physical condition, environment, and care provided. This study proposes a Decision Tree (DT) algorithm optimized using Particle Swarm Optimization (PSO) to more accurately predict Etawa goat productivity. A case study was conducted at the